Tribal Rifts: A Valuation to the Extent of Criminal Justice System and Bodong System in Resolving Crimes and Disputes in the ASEAN Region - Domingo, Noemi (JPAIR Multidisciplinary Research, 2017)
The Cordillera Administrative Region’s way of resolving crimes and disputes between two tribes is in accordance with their Bodong system wherein the codified and published Pagta or "the law of the Bodong" (literally translated "peace covenant or pact") is Kalinga’s number one cultural and historical contribution to the country’s National Cultural Treasure. The study determined the extent of Criminal Justice System and Bodong System in resolving crimes and disputes encountered by tribes who are in conflict. The researcher used the case study method wherein the basis for its concept is the theoretical framework, socio-cultural theory and grounded theory and self-report data with convenience sampling. "Semi-structured interviews, narrative response and blog discussions" were also used. 50% of the respondents stand for the statement that bodong system is bound to resolve cases that involve murder, land disputes, loss of property and other violations. Hence, the Cordillera Administrative Region’s urge in pursuing in the legalization and government recognition of the Bodong System has put an ease with the lengthy trials of the Criminal Justice System. The Cordilleran leaders’ initiative to organize PEACE SUMMIT every year is an effective way of informing people of Cordillera the essence of Bodong in their life not just a mere machinery, but rather a system.